5‐HT3 receptors antagonists reduce serotonin‐induced scratching in mice. (31st March 2015) - Ostadhadi, Sattar; Kordjazy, Nastaran; Haj‐Mirzaian, Arya; Mansouri, Parvin; Dehpour, Ahmad Reza
Abstract Serotonin (5‐hydroxytryptamine, 5‐HT) acts as a pruritogen in humans and animals, but the mechanisms of action through that serotonin induces itch response have not been extensively discovered. In our study, we attempted to investigate the role of 5‐HT3 receptors in scratching behavior due to intradermal serotonin injection. Intradermal injection of serotonin (14.1–235 nmol/site) into the nape of the neck of mice was performed to elicit itch. Scratching behavior was evaluated by measuring the number of bouts during 60 min after injection. We evaluated the effect of intraperitoneal pretreatment with ondansetron and tropisetron (0.1, 0.3, and 1 mg/kg) on itch induced by serotonin. Also, intradermal ondansetron and tropisetron at doses 50, 100, and 200 nmol/site were concurrently administrated with serotonin. Serotonin produced a significant enhancement in scratching at dose 141 nmol/site. Concurrent administration of ondansetron (50, 100, and 200 nmol/site) and tropisetron (100 and 200 nmol/site) with serotonin reduced scratching activity compared to the animals that only received serotonin. Also, pretreatment with intraperitoneal ondansetron and tropisetron (0.3 and 1 mg/kg) 30 min before serotonin attenuated the itch response. We showed that the scratching induced by intradermal serotonin is mediated by 5‐HT3 receptors subtype. It can be concluded that 5‐HT3 may play a role in mediating serotonin‐associated itch responses, and we introduce 5‐HT3 receptors as possible targets for antipruritic agents.